Pemikiran Progresif Mahasiswa terhadap Hadis-hadis Misoginis (Studi Kasus terhadap Mahasiswa UIN Syarif Hidayatullah Jakarta) - Ahmad Fudhaili (Refleksi, 2021)
This study focuses on the discussion of students' progressive thinking towards traditions that are claimed to be misogynistic. The purpose of this study was to determine the extent to which students understand and accept the hadiths that are claimed to be misogynistic. The object or sample of this research is the student of Hadith Science Study Program, Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta. This research is a type of quantitative research using experimental research. In this study, in addition to data obtained through field research, data were also obtained through library research. The time of the research was carried out from January to September 2020 starting from preparation, observation, research, and collecting the data needed in this study. Based on the results of this study, it was found that the level of literacy or understanding and acceptance of students of the UIN Jakarta Hadith Science Study Program towards misogyny traditions was still relatively poor. This is based on the answers given by respondents who still choose gender-biased answers.